2013
DOI: 10.1016/j.joca.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between cartilage and bone biomarkers and incidence of radiographic knee osteoarthritis (RKOA) in UK females: a prospective study

Abstract: Aggrecan and COMP circulating levels contribute to identification of phenotype-specific RKOA incidence. These data suggest potentially protective role of aggrecan in cartilage loss, as measured by JSN. High COMP levels are risk factors for development of RKOA, as assessed by K/L scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…Twenty two cohort studies which were either population-based (n = 14) [5][6][7][10][11][12][13][14][15][16][17][18][19][20] or hospital-based (n = 8) [21][22][23][24][25][26][27][28] cohorts and three randomized clinical trials [29][30][31] with follow-up time ranged from 1 to 15 years were included. Most of the studies included both genders and only 6 studies evaluated OA in women solely [12,17,19,20,30,31]. Incidence of knee and hip OA was studied in 8 and 6 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty two cohort studies which were either population-based (n = 14) [5][6][7][10][11][12][13][14][15][16][17][18][19][20] or hospital-based (n = 8) [21][22][23][24][25][26][27][28] cohorts and three randomized clinical trials [29][30][31] with follow-up time ranged from 1 to 15 years were included. Most of the studies included both genders and only 6 studies evaluated OA in women solely [12,17,19,20,30,31]. Incidence of knee and hip OA was studied in 8 and 6 studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported the estimates for different definition of OA. Incidence of OA defined by a radiographic KL scoring system (KL ≥ 2) was used in eight studies [5,7,10,[12][13][14]17,20] among which two studies [7,10] added TJR as grade 5 of KL scoring. In four studies the assessment of OA incidence was based on the measurements of the joint space width [12][13][14]20], while modified Croft scoring was used in one study to defined OA incidence [19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies (three longitudinal studies; two crosssectional studies) reported subgroups of participants with alterations in bone and cartilage metabolism within the knee joint [20,22,32 [34]. Evidence from these papers also suggests this may constitute more than a single phenotype, including some rare variations.…”
Section: Bone and Cartilage Metabolismsmentioning
confidence: 99%